Profound Learning and Living: An Exploratory Delphi Study - Davin J Carr-Chellman; Michael Kroth (Adult Education Research Conference, 2018)
This study, using Delphi methodology conceptualizes the qualities of profound learning, the profound learner, and profound living.
Keywords: Profound learning; profound living; profundity; deep